Serbuk effervescent kombinasi ekstrak buah pare (Momordica charantia L.) dan buncis (Phaseolus vulgaris L.) sebagai nutraseutikal - Rima Hayati; Amelia Sari; Nur Alfina (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2019)
Bitter melon and beans contain flavonoids which have the potential as antidiabetic agents. The combination of ethanolic extract of bitter melon (Momordica charantia L) and bean (Phaseolus vulgaris L) given orally has been investigated and proven to reduce blood glucose levels in mice. This study aims to formulate a combination of ethanol extract of bitter melon and beans with variations in sweetener concentration. This research is an experimental study. Effervescent powder made in two formulas with variations in sucralose and aspartame. Formula 1 (F1) uses a concentration of 0,20% sucralose and 0,5% aspartame and formula (F2) using a concentration of 0.24% sucralose and 0,75% aspartame. The organoleptic test indicated the powder produced is brownish white, has the smell of sucralose and aspartame and has a sweet taste (F1, F2). Flow rates are 0,6 g / sec (F1) and 0,5 g / sec (F2) with the category